Pile capacity determination by static load tests - Prelligera, Flor Angel G.
In pile foundation designs, the ultimate capacity of the piles must agree with the design capacity assumptions. To ascertain this, in-situ loading test such as static load testing is often performed. In this kind of test, piles should be loaded to failure and the load at which it fails is termed as the ultimate load. However, due to time constraints and practicality, piles are not often loaded to failure especially In Philippine local setting. Engineers usually conduct an alternative method to determine the behavior of piles loaded up to failure from static load test data at more or less twice the design load in order to have an approximation of the ultimate axial capacity of design piles. In this study, the applicability of ten interpretation methods is analyzed based on axial static load testing data. Advantages and disadvantages of each method are discussed and explored. Results of the analyses show that Davisson's method yields the most conservative ultimate capacity and Chin-Kondner's method however produced the largest value of ultimate capacity.